UPAYA UNDP (UNITED NATIONS DEVELOPMENT PROGRAMME) DALAM MEMAJUKAN DEMOKRASI DI MYANMAR - Muslina "; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research explains about the efforts of UNDP in progressing democracy for Myan-mar. Myanmar is a country governed by the rule of the military junta during the approximately fifty years. The presence of UNDP in Myanmar is to advance democracy in Myanmar previously are stagnant. This analysis aims to determine what the steps of UNDP to progress democracy in Myanmar. The theory in this research is the theory of democratic transition , which leads to the democratization process of the shift from an authoritarian government to the democratic government that passes through a complex path , including the transition that took place in Myanmar . The Analysis of this research used data collection techniques , both qualitative data and theoretical data. Based on the result of UNDP and Democracy in Myanmar are to accommodate the en-tire interest, either from the Government or from the party of Myanmar pro-democracy group democracy in the form of dialogue, strengtheninglocal government, as well as provide technical assistance, facilitate and support thefinancial investments as well as strength-en the educational system.Keywords: UNDP, Myanmar, Progress, Democracy